The challenges and opportunities of social connection when hearing derogatory and threatening voices: A thematic analysis with patients experiencing psychosis. (30th October 2020) - Sheaves, Bryony; Johns, Louise; Černis, Emma; Griffith, Laura; ,; Freeman, Daniel
Abstract : Objectives: Relationships with other people are important determinants of the course of psychosis, yet social isolation is common. This study sought to learn about the patient experience of being around other people when hearing derogatory and threatening voices (DTVs). Design: A qualitative interview study. Methods: Fifteen participants with experience of hearing DTVs in the context of non‐affective psychosis were recruited from NHS services. Data were obtained by semi‐structured interviews and analysed using thematic analysis. Results: Three themes were identified: (1) reasons why interacting with people is difficult when hearing DTVs; (2) the relationship between social connection and DTVs; and (3) factors which enable voice hearers to connect with others. A further ten sub‐themes are outlined as reasons why hearing DTVs led to lower social connection, including difficulties during conversations (e.g., the concentration required is hard ), negative expectations of interactions (e.g., fearing negative judgement from others ), and difficulties sharing experiences of voices (e.g., people will be hurt or upset if I tell them about the voices ). Isolation was a common response to hearing DTVs but also a time of vulnerability for hearing voices. Managing the challenges of interacting with people led to some improvements in DTVs. Conclusions: There are understandable reasons why hearing DTVs leads to lower social connection. Yet isolating oneself can also be a time of vulnerability for DTVs. Social connection might be one vehicle for disengaging from and disputing derogatory and threatening voice content. The effect on voice hearing of social recovery interventions warrants further investigation. Practitioner points: Participants shared 10 reasons why being around people is challenging when hearing derogatory and threatening voices. These typically affected both daily social experiences and contact with clinicians. Common initial responses to hearing DTVs were to reduce contact with people, experience difficulties connecting during conversations and to avoid sharing the experience of voice hearing. However, social isolation was a time of vulnerability to DTVs, and hence, increasing social connection might be a target for interventions. A range of factors enabled voice hearers to manage social situations, for example: the fostering of trust, self‐acceptance, learning when it is better to stay at home, and developing a narrative to explain voice hearing to others. Addressing the barriers to connecting with others might have an important role in personal recovery from voice hearing.